Immune imbalance and autoimmune mechanisms in plasma cell mastitis: current perspectives - Xue, Bingjie; Jiang, Yuang; Lei, Yan; Liu, Xin; Li, Jing; Li, Yunxiang; Zhang, Binyue; Wang, Yanhong; Jia, Hongyan (Frontiers in Cell and Developmental Biology, 2026)
Plasma cell mastitis (PCM), also termed ductal dilatation or periductal mastitis (PDM), is a benign, non-bacterial inflammatory breast disorder predominantly affecting non-lactating women. Its incidence continues to rise, yet diagnosis and therapeutic approaches remain under development. Consequently, elucidating the pathogenesis is essential for identifying the disease’s root cause and facilitating breakthroughs. PCM is increasingly regarded as an autoimmune disorder, highlighting the crucial role of immune factors in its development; however, the precise immune mechanisms involved remain incompletely understood. Against these backgrounds, this review aims to: (1) discuss the contributions of various innate and adaptive immune cells within the PCM-associated immune microenvironment; (2) describe the relationship between imbalances in key immune cells (including M1/M2 macrophages, Th1/Th2 lymphocytes, Th17/Treg cells) and the progression of PCM; (3) explore potential future research areas, the underlying immunopathogenesis of PCM, and prospective therapeutic targets, the activation of the complement system, regulation of immune homeostasis, the role of immune cell circadian rhythms, and modulation of key immune pathways.